IPTEKS PENERAPAN DAN MANFAAT TEKNOLOGI INFORMASI TERHADAP PROSES BISNIS PERBANKAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG MANADO - Anis, Valencia Matthew; Tangkuman, Steven J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The use of information technology plays an important role in the company's business processes. One of the success factors of company performance is the optimal use or application of information technology. Especially in banking business process activities, the use of information technology is one of the weapons in competition in the banking business world. In this article Bank BRI, which is one of the largest banking companies in Indonesia, also relies on information technology in the continuity of its business processes. In this article, we will discuss about the application of the Bank BRI Manado branch office’s Information Technology and its benefits in the continuity of banking business processes. In this case the BRI bank Manado branch office uses a variety of information systems in the banking business processes that will be explained in this article.Keywords : Business Processes, Information Technology, Banking business, Information System, Bank